The Role of Conscious Attention in How Weight Serves as an Embodiment of Importance. (December 2017) - Zestcott, Colin A.; Stone, Jeff; Landau, Mark J.
Inconsistency among findings in the embodied cognition literature suggests a need for theoretical boundary conditions. The current research proposes that conscious attention of a bodily state can moderate its influence on social judgment. Three studies tested this possibility in the case of the demonstrated effect of weight sensations on judgments of an abstract idea's importance. Studies 1 and 2 showed that participants rated a topic as more important when holding a moderately heavy, compared with light, clipboard. However, when the clipboard was very heavy, participants rated the survey topic as less important compared with when the clipboard was moderately heavy. The differences in importance ratings were not caused by derogation of the topic or the activation of a different metaphor. In Study 3, the importance rating difference between light and moderately heavy clipboards was eliminated by explicitly drawing perceiver's attention to the clipboard's weight. Implications and future directions are discussed.